Titration effectiveness of two autoadjustable continuous positive airway pressure devices driven by different algorithms in patients with obstructive sleep apnoea. Issue 6 (25th July 2013) - Damiani, Mario Francesco; Quaranta, Vitaliano Nicola; Tedeschi, Ersilia; Drigo, Riccardo; Ranieri, Teresa; Carratù, Pierluigi; Resta, Onofrio
Abstract Background and objective Nocturnal application of continuous positive airway pressure (CPAP) is the standard treatment for patients with obstructive sleep apnoea (OSA). Determination of the therapeutic pressure (CPAP titration) is usually performed by a technician in the sleep laboratory during attended polysomnography. One possible alternative to manual titration is automated titration. Indeed, during the last 15 years, devices have been developed that deliver autoadjustable CPAP (A‐CPAP). The aim of the present study was to compare the titration effectiveness of two A‐CPAP devices using different flow‐based algorithms in patients with OSA. Methods This is a randomized study; 79 subjects underwent two consecutive unattended home A‐CPAP titration nights with two different devices (Autoset Resmed; Remstar Auto Respironics); during the third and the fourth night, patients underwent portable monitoring in the sleep laboratory during fixed CPAP at the A‐CPAP recommended pressure. Results Bland Altman plots showed good agreement between the recommended median and maximal pressure levels obtained with the two devices. A significant improvement was observed in all the sleep parameters by both A‐CPAP machines to a similar degree. Conclusions It was observed that the two A‐CPAP devices using different algorithms are equally effective in initial titration of CPAP.